2009
DOI: 10.1159/000242356
|View full text |Cite
|
Sign up to set email alerts
|

Structural and IgE Binding Analyses of Recombinant Der p 2 Expressed from the Hosts <i>Escherichia coli</i> and <i>Pichia pastoris</i>

Abstract: Background: The house dust mite allergen Der p 2 is one of the most important indoor allergens associated with allergic disease. Recombinant Der (rDer) p 2 with high IgE binding activity can be readily produced in Escherichia coli and Pichia pastoris, but the structure and IgE binding of the different methods of preparation have not been compared. Methods: Secondary structure was assessed by circular dichroism (CD). Intrinsic fluorescence and hydrophobic probe (1-anilinonaphthalene 8-sulphonic acid, ANS) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 65 publications
3
20
1
Order By: Relevance
“…Altogether, our data demonstrate that the rDer p 2 produced in P. pastoris more closely resembles nDer p 2 when compared to the E. coli -derived rDer p 2. These results differ from those obtained in a recent study indicating that Der p 2 secreted by P. pastoris has a mainly unordered structure [31]. Explanations for such discrepancies are unclear but may originate from differences in yeast strains as well as the expression and purification protocols used.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Altogether, our data demonstrate that the rDer p 2 produced in P. pastoris more closely resembles nDer p 2 when compared to the E. coli -derived rDer p 2. These results differ from those obtained in a recent study indicating that Der p 2 secreted by P. pastoris has a mainly unordered structure [31]. Explanations for such discrepancies are unclear but may originate from differences in yeast strains as well as the expression and purification protocols used.…”
Section: Discussioncontrasting
confidence: 95%
“…Along with other authors, we reported previously that the immunoreactivity and allergenicity of the Der p 2 molecule are still preserved to some extent despite incorrect folding [31,37,51,53], likely due to the presence of linear IgE epitopes [55]. Our results confirm a direct link between correct cysteine pairing and both molecular homogeneity and stability evaluated by resistance to heat denaturation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Yeast-expressed recombinant Der p 2 (rDer p 2) was produced as previously described 10 from a single colony of transformed P. pastoris KM71H strain containing Der p 2 variant cDNA and grown in buffered complex media containing glycerol (BMGY) in a ratio of 1:100 at 30°C with shaking until O.D.600 nm of 20.0-25.0. Cells were harvested and resuspended in a solution containing 1% yeast, 2% casamino acid, 1% asparagine, 0.34% Yeast Nitrogen Base, 4×10 -5 % biotin, and 0.5% methanol (YCM) at a 10-fold more concentration and were grown for 72 hours at 30°C.…”
Section: Allergensmentioning
confidence: 99%
“…10 According to this protocol, 1-anilinonaphthalene 8-sulfonic acid (1,8-ANS) (Sigma, St. Louis, MO, USA) binding to measure the hydrophobic binding capacity of Der p 2 was conducted as before 10 with 1,8-ANS dissolved in methanol at a concentration determined spectrophotometrically using a molar extinction coefficient of 8,000 M/cm at 372 nm. For assay, 3.5 µM natural Der p 2 (nDer p 2) or rDer p 2 variants were mixed with 200 µM ANS for 10 minutes at 25°C.…”
mentioning
confidence: 99%